2021
DOI: 10.1371/journal.pone.0249631
|View full text |Cite
|
Sign up to set email alerts
|

ddcP, pstB, and excess D-lactate impact synergism between vancomycin and chlorhexidine against Enterococcus faecium 1,231,410

Abstract: Vancomycin-resistant enterococci (VRE) are important nosocomial pathogens that cause life-threatening infections. To control hospital-associated infections, skin antisepsis and bathing utilizing chlorhexidine is recommended for VRE patients in acute care hospitals. Previously, we reported that exposure to inhibitory chlorhexidine levels induced the expression of vancomycin resistance genes in VanA-type Enterococcus faecium. However, vancomycin susceptibility actually increased for VanA-type E. faecium in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…The base-evolved clones had the largest number of mutations overall (Table 1). All but one of the eight strains from pH 9.0 evolution showed a mutation in a gene involving phosphate metabolism: pstB, pstB2 (both encoding a phosphate ATP-binding protein of an ABC transporter (47, 48)and pyrR (encoding a bifunctional pryimidine transcriptional regulator/ uracil phosphribosyltransferase (4951)). A majority of these mutations were frameshift or nonsense codons that would knock out the gene.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The base-evolved clones had the largest number of mutations overall (Table 1). All but one of the eight strains from pH 9.0 evolution showed a mutation in a gene involving phosphate metabolism: pstB, pstB2 (both encoding a phosphate ATP-binding protein of an ABC transporter (47, 48)and pyrR (encoding a bifunctional pryimidine transcriptional regulator/ uracil phosphribosyltransferase (4951)). A majority of these mutations were frameshift or nonsense codons that would knock out the gene.…”
Section: Resultsmentioning
confidence: 99%
“…While no change in antibiotic resistance was found under our conditions, in clinical studies small-colony variants are associated with drug resistance and increased virulence (39, 40, 55). Mutations in pst genes are associated with clinical virulence (Lieberman) and altered antibiotic resistance (48). In soil and plant root communities, phosphate release is maximized at pH below 7 (56, 57) and has been proposed to contribute to bacterial pH regulation (58).…”
Section: Discussionmentioning
confidence: 99%
“…In E. faecalis , the pst operon consists of five pst genes ( pstS , C , A , BA and BB ) and phoU . In E. faecium , a S199L amino acid substitution in PstBB confers protection against killing by vancomycin and chlorhexidine co‐treatment (Bhardwaj et al, 2021), while in S. pneumoniae deletion of pstB results in a decrease in uptake of phosphate and reduced autolysis, likely due to altered amidase activity (Novak et al, 1999). Perhaps, then it is not a coincidence that we observed an amino acid substitution in PstBB alongside a mutation in the putative autolysin, N ‐acetylmuramoyl‐L‐amidase, as both may be working together to reduce autolytic activity and rescue tolerance in the croRS 5BS mutant (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Bhardwaj et al (2017) found that CHX stress induced the expression of the VanAtype vancomycin resistance genes and genes associated with decreased susceptibility to daptomycin (liaXYZ) in E. faecium. However, vancomycin susceptibility was actually increased for the VanA-positive E. faecium in the presence of subinhibitory concentrations of CHX, revealing a CHX-vancomycin synergy (Bhardwaj et al, 2017(Bhardwaj et al, , 2021. Excess of D-lactate contributed to this synergism, whereas the deletion of the gene ddcP, encoding a membrane-bound carboxypeptidase, and a mutation (S199L) on an ATPase of phosphate-specific transporter, encoded by gene pstB, conferred a survival advantage in the presence of both antimicrobials (Bhardwaj et al, 2017(Bhardwaj et al, , 2021.…”
Section: Co-and Cross-resistance Between Cationic Biocides and Other ...mentioning
confidence: 99%
“…However, vancomycin susceptibility was actually increased for the VanA-positive E. faecium in the presence of subinhibitory concentrations of CHX, revealing a CHX-vancomycin synergy (Bhardwaj et al, 2017(Bhardwaj et al, , 2021. Excess of D-lactate contributed to this synergism, whereas the deletion of the gene ddcP, encoding a membrane-bound carboxypeptidase, and a mutation (S199L) on an ATPase of phosphate-specific transporter, encoded by gene pstB, conferred a survival advantage in the presence of both antimicrobials (Bhardwaj et al, 2017(Bhardwaj et al, , 2021. Nonetheless, the occurrence of a possible cross-resistance between vancomycin and CBs, including CHX, is still controversial.…”
Section: Co-and Cross-resistance Between Cationic Biocides and Other ...mentioning
confidence: 99%